Design of cable-driven active flexibly-constrained pairs with non-linear stiffness in multiple directions - Naoto KIMURA; Nobuyuki IWATSUKI (Mechanical Engineering Journal, 2022)
In order to synthesize a human-friendly flexible machine with a simple structure, the flexibly constrained pair (FCP), which is a passive kinematic pair with a flexible kinematic constraint in multiple directions, has been proposed as a novel type of a kinematic pair (Kimura et al, 2021a). However, structures of robots with FCPs must be limited to only closed-loop mechanisms because the FCP is a passive kinematic pair. As a novel kinematic pair to solve this problem, the active flexibly constrained pair (AFCP) is proposed in this paper. This kinematic pair is used as an underactuated active joint mechanism antagonistically driven with several active elastic elements. As active elastic elements for the AFCP, reeled elastic wires with linear elasticity are used to simplify its design and control. In order to design it, a method to optimally arrange reeled elastic wires between the links of the underactuated joint based on a transmission index is proposed. Besides, a method to specify the stiffness required to perform the task in active degrees of freedom (DOF) and the stiffness to balance both flexibility and motion accuracy in passive DOF is proposed. In addition, a method to analyze the kinetostatic motion between the links is proposed to evaluate the motion accuracy of the designed AFCP. As examples, the AFCP with 1-axial main rotation and the AFCP with 1-axial translation along the specified trajectory are designed and analyzed. Finally, they are prototyped, and their performances are examined by experiments.